Progesterone (PR), Oestrogen (ER-alpha and ER-beta) and Oxytocin (OTR) Gene Expression in the Oviduct and Uterus of Pregnant and Non-pregnant Bitches - Derussi, A. A. P. [UNESP]; de Souza, R. W. A. [UNESP]; Volpato, R. [UNESP]; Guaitolini, C. R. F. [UNESP]; Ackermann, C. L. [UNESP]; Taffarel, M. O. [UNESP]; Cardoso, G. S. [UNESP]; Dal-Pai-Silva, M. [UNESP]; Lopes, Maria Denise [UNESP] (Wiley-Blackwell, 2012)
Contents The aim was to assess hormone receptor gene expression in the oviduct and uterus during canine pregnancy. Nineteen pregnant bitches divided into four groups were ovariohysterectomized (OVH) at either day 8, 12, 21 or 60 of pregnancy, and five non-pregnant females underwent OVH 12days after the pre-ovulatory Luteinizant Hormone (LH) surge and served as controls. RT-qPCR for progesterone (PR), oestrogen (ER-a and ER-beta) and oxytocin (OTR) receptors was performed on the oviduct and uterine tissue. The mRNA PR expression in the uterus during early stages of pregnancy and the luteal phase was higher than at other times. The mRNA ER-beta expression in the oviduct during early pregnancy was less than in non-pregnant bitches. In the uterus, the mRNA ER-beta expression was higher in the initial stages of pregnancy. The ER-a expression was higher in the oviduct and uterus in advanced stages of pregnancy. The mRNA OTR expression in the oviduct was lower than in the uterus in control group. The expression of this receptor in oviduct and the uterus was higher in the final stages of pregnancy, when compared with other phases. These data suggested that the serum progesterone concentrations probably exert a direct control on the PR and ER (a and beta) expression and indirectly on OTR expression in the bitch oviduct and uterus.